A systematic review of the utility of assistive technologies for SEND students in schools - Mukhtarkyzy, Kaussar; Smagulova, Laura; Tokzhigitova, Ainur; Serikbayeva, Nurgul; Sayakov, Olzhas; Turkmenbayev, Asset; Assilbayeva, Rakhila (Frontiers in Education, 2025)
The systematic review investigates the effect of various educational technologies on the learning outcomes of diverse student populations, particularly focusing on assistive technology interventions for students with disabilities. The comprehensive analysis covers literature from 2012 to 2023. The study highlights the potential of AR and assistive technologies in fostering inclusive and engaging learning environments. Despite positive findings, the review emphasizes the imperative for further research to refine the implementation of these technologies and enhance their effectiveness. The systematic review of five databases provides crucial insights into the effectiveness of various assistive technologies. Mobile devices, iPads, and AR interventions emerge as frequently utilized tools. Research activity peaked in 2013 and 2018 and subsequently declined. Twelve studies focus on Autism Spectrum Disorder and emphasize the prioritization of ASD in assistive technology interventions. The research highlights the importance of adopting a holistic perspective on educational inclusion, emphasizing collaborative efforts among teachers, diverse teaching methods, and technology integration. Despite the promise shown by assistive technologies, the review acknowledges their limitations and advocates for ongoing research and innovation to refine their application across diverse educational contexts. The findings stress the importance of a nuanced interpretation of evidence, considering the challenges posed by the limited number of eligible studies. The review calls for careful consideration of future research directions to bolster the comprehensiveness and reliability of evidence synthesis in assistive technology interventions for students with disabilities.